The Influence of Work Environment and Work Discipline on the Performance of No-Sew Employees at PT. Adis Dimension Footwear, Tangerang Regency - Deyana, Deyana; Purwanto, Agus; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to analyze the influence of the work environment and work discipline on the performance of employees in the No Sew department at PT Adis Dimension Footwear, Tangerang Regency. This study used a quantitative approach with descriptive methods. The population in this study consisted of 63 employees, all of whom were sampled using a saturated sampling technique. The research instrument used a Likert scale questionnaire. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²) using SPSS version 26. The results showed that the work environment and work discipline, both partially and simultaneously, significantly influenced employee performance. This study implies that improving the quality of the physical and non-physical work environment and the consistent implementation of work discipline can increase employee productivity and work quality.